2013
DOI: 10.1089/lap.2013.0065
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Intestinal and Mesenteric Injuries with Small Bowel Volvulus Following Use of Barbed Suture During Laparoscopic Myomectomy

Abstract: This is a case report of a patient who developed major intestinal complications after the utilization of barbed sutures for an off-label indication. The report serves as a warning for patients and surgeons of the potential injuries that may be caused by the use of new products in unapproved indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…[21][22][23][24] Sixteen studies referred to laparoscopic cases while 3 studies to robotic cases. In total, 1991 patients were included.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24] Sixteen studies referred to laparoscopic cases while 3 studies to robotic cases. In total, 1991 patients were included.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have indicated that barbs can cause small bowel injury [21] and that within 30 days after total laparoscopic hysterectomy, small bowel obstruction can develop [22], possibly because the laparoscope can disrupt the suture line, allowing the barbs to get caught in the digestive tract and greater omentum. In addition, barbs left exposed outside the uterus after the suture thread is cut can become entangled in the digestive tract and cause small bowel obstruction, especially when the suture thread is tensed before being cut, drawing the thread into the myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…TAPP repair invariably requires peritoneal closure because the bowel may adhere to the exposed prosthetic mesh. However, use of the barbed suture is also associated with the risk of small bowel entrapment when the free end of the thread is cut long; potentially severe postoperative complications, such as intestinal obstruction, have been reported in such circumstances (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). To prevent these complications, the barbed suture may be additionally trimmed and buried using either absorbable sutures, or surgical clips (19).…”
Section: Discussionmentioning
confidence: 99%